Use of tranexamic acid in dogs with primary immune thrombocytopenia: A feasibility study - Olivares, Gerard; Sharman, Mellora; Miller, Rachel; Kisielewicz, Caroline; Seth, Mayank (Frontiers in Veterinary Science, 2023)
Objective Feasibility study evaluate the use and safety of tranexamic acid in addition to standard therapy in dogs with primary immune thrombocytopenia (ITP). Design Cohort feasibility study. Ten dogs diagnosed with primary ITP received standard therapy for ITP including corticosteroids, a single dose of vincristine, and omeprazole. Patients were randomized to be part of the control group (n=6) or receive tranexamic acid (TXA group, n=4). Key findings The mean time from the start of treatment until remission was 5 days in the TXA group and 6 days in the control group (P=0.69). Two dogs, one in each group, did not achieve remission. Clinical bleeding scores were not significantly different between groups (p=0.43) and the median blood volume administered was 37.5 ml/kg for the TXA group and 9.72 ml/kg for the control group (p=0.084). Three out of four dogs receiving TXA at 20 mg/kg IV developed vomiting within 15 minutes of administration and required dose reductions to 15 or 10 mg/kg IV. Conclusion Tranexamic acid did not confer a clinical benefit in this small cohort, and was associated with a high incidence of vomiting. This study provides useful information for the design of future trials in dogs with ITP receiving tranexamic acid including outcome measures and safety.